Chlamydia Secret Enemy From Past to Present - Sarier, Mehmet (Infectious Diseases, 2023)
Chlamydia infections continue to pose a serious socioeconomic burden globally. Despite advances in diagnostic tests in recent decades, chlamydial infections still cannot be controlled, neither in developed countries nor in developing countries. Chlamydial infections date back to the beginning of recorded human history. Trachoma caused by Chlamydia trachomatis, which progresses to blindness, is mentioned in ancient Chinese inscriptions and Egyptian scrolls. Today, we must better apply our knowledge against this clever and evolving obligate intracellular parasitic microorganism. Chlamydia - Secret Enemy from Past to Present examines chlamydial infections using a comprehensive multidisciplinary approach. It discusses the microbiology, clinical presentation, and current approaches in the diagnosis and treatment management of chlamydial infection from the viewpoint of different clinics as well as includes relevant and recent literature.